Guinness world records 2021 (Guinness World Records Limited, 2020)
All aboard Guinness World Records 2021 for a life-changing journey of discovery! This year, we're devoting a chapter to the history of exploration, starting with the story of the very first circumnavigation, along with our History of Adventure timeline, featuring a host of remarkable achievements. The fully revised and updated best-seller is packed with thousands of incredible new feats across the widest spectrum of topics, providing a whistle-stop tour of our superlative universe. Our ever-expanding pool of international consultants and experts help us make sense of the world around us and the cosmos beyond. So join us as we embark on a voyage through the vast panorama of record-breaking in 12 fact-packed chapters: - Travel through the Solar System and see the planets come to life with a free augmented-reality feature - Encounter the cutest, weirdest, most dangerous and exotic creatures on our home planet - Meet the world's tallest, shortest, hairiest and heaviest humans - Marvel at the latest high scores, speed runs and players at the top of their game in eSports and beyond - Get the lowdown on the world's most successful and prolific actors, musicians, TV stars and influencers - Review the greatest sports achievements from the past year and celebrate today's top athletes We've also selected the best of the newly approved claims from the 50,000 applications received from the public over the past 12 months. But don't just be a tourist: try some of our specially created try-at-home challenges that could see YOU listed in the world-famous book of records. If you want to be one of those lucky few, check out our Against the Clock chapter - we might even see you in next year's edition!